An Approach To Media Multiplexity In Superior-Subordinate Relations In Government Institutions - Mutia Susana (Universitas Medan Area, 2023)
This paper aims to show how the use of multiple media (multimodality) has an effect on increasing the closeness of relationships. The problems are focused on improving relationships that are usually